(untitled) (Annals of Medical Research, 2022)
Aim: To evaluate the effect of preoperative blood count parameters and pathological features on recurrence in patients who underwent Radical Nephroureterectomy (RNU) and Bladder Cuff Resection for Upper Urinary Tract Urothelial Cancer (UTUC). Material and Methods: The data of patients who underwent RNU for UTUC were reviewed retrospectively. According to the follow-up data, the patients were divided into 2 groups as recurrence and non-recurrence. It was examined whether there was a difference between the groups in terms of preoperative blood count parameters (neutrophil, lymphocyte, eosinophil, monocytes, neutrophil-lymphocyte ratio, and platelet-lymphocyte ratio) and final pathological features. A p<0.05 was considered statistically significant. Results: A total of 64 patients were included in the study. Recurrence developed in 24 patients during follow-up. Age (p=0.039), neutrophil-lymphocyte ratio (p=0.026), history of bladder cancer (p=0.004), pathological stage (p=0.03), multifocality (p=0.007), positive bladder cuff (p=0.006) and surgical margin positivity (p=0.029) was found to be significantly different in the recurrence group compared to the non-recurrence group. Conclusion: In addition to pathological features, preoperative Neutrophil-Lymphocyte ratio may be associated with recurrence in patients undergoing UTUC and RNU. It should be supported by studies with a larger number of patients.